Strong and persistent correlation between baseline and follow-up HIV-DNA levels and residual viremia in a population of naïve patients with more than 4 years of effective antiretroviral therapy. (March 2015) - Parisi, S.G.; Sarmati, L.; Andreis, S.; Scaggiante, R.; Cruciani, M.; Ferretto, R.; Manfrin, V.; Basso, M.; Andreoni, M.; Mengoli, C.; Palù, G.
Abstract: In a longitudinal study on 181 naïve patients who responded to therapy (mean follow-up 4 years), high baseline human immunodeficiency virus (HIV)-RNA values correlated with high levels of cellular HIV-DNA at all time points (p < 0.0001, p 0.045, p 0.0055, and p 0.0025, respectively) and negatively correlated with undetectable residual viremia (URV; <2.5 copies/mL) at T1, T2, and T3 (p 0.026, p 0.0149, and p 0.0002, respectively). Baseline high HIV-DNA levels predicted the persistence of high values (p 0.0001) and negatively correlated with URV (p 0.0254, p 0.0481, and p 0.0085). These results suggest that baseline viral load, cellular HIV-DNA, and URV were strongly correlated over long-term follow-up of antiretroviral therapy responders.